Kemampuan dan Kesulitan Mahasiswa Program Studi Pendidikan Bahasa Indonesia Universitas Bengkulu dalam Menulis Proposal Penelitian Skripsi - Susetyo Susetyo; Noermanzah Noermanzah (Silampari Bisa: Jurnal Penelitian Pendidikan Bahasa Indonesia, Daerah, dan Asing, 2020)
Students of the Indonesian Language Education Study Program at the University of Bengkulu have difficulty writing a thesis research proposal. This is proven by not many students who passed on time in semester VIII. The purpose of this research is to identify and describe: (1) the ability of students in writing thesis research proposals and (2) the difficulties faced by students in writing thesis research proposals. The method used in this research is descriptive method. The population of this study was all students of semester VII of the Indonesian Language Education Study Program in the 2017/2018 academic year. The sample of this research is 80 students who write thesis research proposals. The data collection techniques were documentation and interview techniques. Data analysis to analyze quantitative data used the percentage formula, while for qualitative data it was analyzed using the Miles and Huberman analysis model with the steps of data reduction analysis, data display, verification, and conclusions. The results showed that the ability to write thesis research proposals for seventh semester students of the Indonesian Language Education Study Program for the academic year 2017/2018 was classified as sufficient qualification. Then, students experience difficulties in compiling proposals in writing problems and problem formulations, writing theoretical foundations and literature reviews, determining research methods, data collection techniques and arranging instruments as well as testing, assessment rubrics, and research data analysis. The seventh semester students of the Indonesian Language Education Study Program at the University of Bengkulu should be assisted so that they really understand how to compile a thesis research proposal so that they can write a research proposal well and in the end students will be able to complete their thesis quickly and on time.